Scaffold-Free Fabrication of Osteoinductive Cellular Constructs Using Mouse Gingiva-Derived Induced Pluripotent Stem Cells - Hiroko Okawa; Hiroki Kayashima; Jun-Ichi Sasaki; Jiro Miura; Yuya Kamano; Yukihiro Kosaka; Satoshi Imazato; Hirofumi Yatani; Takuya Matsumoto; Hiroshi Egusa (Hindawi Limited, 2016)
Three-dimensional (3D) cell constructs are expected to provide osteoinductive materials to develop cell-based therapies for bone regeneration. The proliferation and spontaneous aggregation capability of induced pluripotent stem cells (iPSCs) thus prompted us to fabricate a scaffold-free iPSC construct as a transplantation vehicle. Embryoid bodies of mouse gingival fibroblast-derived iPSCs (GF-iPSCs) were seeded in a cell chamber with a round-bottom well made of a thermoresponsive hydrogel. Collected ball-like cell constructs were cultured in osteogenic induction medium for 30 days with gentle shaking, resulting in significant upregulation of osteogenic marker genes. The constructs consisted of an inner region of unstructured cell mass and an outer osseous tissue region that was surrounded by osteoblast progenitor-like cells. The outer osseous tissue was robustly calcified with elemental calcium and phosphorous as well as hydroxyapatite. Subcutaneous transplantation of the GF-iPSC constructs into immunodeficient mice contributed to extensive ectopic bone formation surrounded by teratoma tissue. These results suggest that mouse GF-iPSCs could facilitate the fabrication of osteoinductive scaffold-free 3D cell constructs, in which the calcified regions and surrounding osteoblasts may function as scaffolds and drivers of osteoinduction, respectively. With incorporation of technologies to inhibit teratoma formation, this system could provide a promising strategy for bone regenerative therapies.